A Case Study of Code Mixing in an EFL Classroom: Evidence from an English Teacher in a Junior High School - Maria Klarita Thein; Erlinda Sonya Pale; Desta Gloria Siahaan (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This study investigates the use of code mixing by an English teacher in an EFL classroom at SMPN 1 Kefamenanu, East Nusa Tenggara, Indonesia. The study aims to identify the types of code mixing employed, determine the dominant type, and explore the pedagogical reasons underlying its use during classroom interaction. A qualitative case study design was employed involving one English teacher teaching ninth-grade students in the academic year 2025/2026. Data were collected through non-participant classroom observation, audio recordings, and an open-ended questionnaire. Classroom interactions were transcribed and analyzed using Muysken’s typology of code mixing, which includes insertion, alternation, and congruent lexicalization. The findings revealed 55 utterances containing code mixing, consisting of insertion and alternation, while congruent lexicalization was absent. Alternation emerged as the dominant type, accounting for 43 utterances (78%), whereas insertion occurred in 12 utterances (22%). The teacher predominantly employed code mixing to facilitate comprehension, clarify instructional content, support students with limited vocabulary, maintain effective classroom communication, and create a more comfortable learning environment. The findings suggest that code mixing functions as a purposeful pedagogical strategy in multilingual EFL classrooms, particularly in contexts where students have limited English proficiency. This study contributes to sociolinguistic research on classroom discourse by providing empirical evidence from a junior high school context in Eastern Indonesia, which remains underrepresented in previous studies.